Internal Communication and its Impact on the Efficient Functioning of the Company - Bednárik, Jaroslav (Political Preferences, 2019)
Communication in the internal environment of the enterprise is the primary tool that is used to transmit information, experience, knowledge, standards and principles which represent an essential pillar of the corporate culture and business management. In the current age of competition, businesses are trying their best to keep their position on the market. They are aware of the fact that behind the success of the company is a satisfied customer. And for the customer to be satisfied as well as the company to have positive outcomes – it's necessary for a company to focus some of their activities on the internal communication. Therefore, the aim of this article is to show the importance of internal communication within the organisation, because through the correctly set process of internal communication the company integrates people, communicates targets and its mission – what nowadays is the key to success. Equally, it's an important part of every corporation communication which forms a part of the whole reputation of the organisation or a business.